Association between smoking cessation and non-alcoholic fatty liver disease using NAFLD liver fat score - Jang, Yun Seo; Joo, Hye Jin; Park, Yu Shin; Park, Eun-Cheol; Jang, Sung-In (Frontiers in Public Health, 2023)
Background: Smoking is well known to be associated with a higher prevalence and incidence of liver diseases such as advanced fibrosis. However, the impact of smoking on developing nonalcoholic fatty liver disease remains controversial, and clinical data on this is limited. Therefore, this study aimed to investigate the association between smoking history and nonalcoholic fatty liver disease (NAFLD). Methods: Data from the Korea National Health and Nutrition Examination Survey 2019-2020 were used for the analysis. NAFLD was diagnosed according to an NAFLD liver fat score of > -0.640. Smoking status was classified as into nonsmokers, ex-smokers, and current smokers. Multiple logistic regression analysis was conducted to examine the association between smoking history and NAFLD in the South Korean population. Results: In total, 9,603 participants were enrolled in this study. The odds ratio (OR) for having NAFLD in ex-smokers and current smokers in males was 1.12 (95% confidence interval [CI]: 0.90-1.41) and 1.38 (95% CI: 1.08-1.76) compared to that in nonsmokers, respectively. The OR increased in magnitude with smoking status. Ex-smokers who ceased smoking for less than 10 years (OR: 1.33, 95% CI: 1.00–1.77) were more likely to have a strong correlation with NAFLD. Furthermore, NAFLD had a dose-dependent positive effect on pack-years, which was 10 to 20 (OR: 1.39, 95% CI: 1.04–1.86) and over 20 (OR: 1.51, 95% CI: 1.14–2.00). Conclusion: This study found that smoking may contribute to NAFLD. Our study suggests cessation of smoking may help management of NAFLD.